Pelvic Pouch Failure: Treatment Options - Lynn, Patricio B.; Brandstetter, Stephen; Schwartzberg, David M. (Clinics in Colon and Rectal Surgery, 2022)
Up to 30% of patients with ulcerative colitis (UC) will require surgical management of their disease during their lifetime. An ileal pouch-anal anastomosis (IPAA) is the gold standard of care, giving patients the ability to be free from UC's bowel disease and avoid a permanent ostomy. Despite surgical advancements, a minority of patients will still experience pouch failure which can be debilitating and often require further surgical interventions. Signs and symptoms of pouch failure should be addressed with the appropriate workup and treatment plans formulated according with the patient's wishes. This article will discuss the identification, workup, and treatment options for pouch failure after IPAA.
Keywords: ulcerative colitis; total proctocolectomy; ileal pouch-anal anastomosis; redo pouch; pouch failure